2016
DOI: 10.1039/c6cc02488b
|View full text |Cite
|
Sign up to set email alerts
|

2,6-Diiminopiperidin-1-ol: an overlooked motif relevant to uranyl and transition metal binding on poly(amidoxime) adsorbents

Abstract: Glutardiamidoxime, a structural motif on sorbents used in uranium extraction from seawater, was discovered to cyclize in situ at room temperature to 2,6-diimino-piperidin-1-ol in the presence of uranyl nitrate. The new diimino motif was also generated when exposed to competing transition metals Cu(ii) and Ni(ii). Multinuclear μ-O bridged U(vi), Cu(ii), and Ni(ii) complexes featuring bound diimino ligands were isolated.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(17 citation statements)
references
References 29 publications
1
15
0
Order By: Relevance
“…Similar multinuclear uranyl complexes were observed during crystallization of glutardiamidoxime with UO 2 (NO 3 ) 2 , where the metal nitrate induced in situ cyclization of the ligand to form a bridged dinuclear species (Figure 17). 132 While DFT and small molecule results are consistent with each other, it is worth noting they are performed under idealized conditions and may not be representative of a complex and dynamic system, as is the case for a polymer adsorbent deployed in seawater.…”
Section: Synthetic Polymersmentioning
confidence: 61%
See 1 more Smart Citation
“…Similar multinuclear uranyl complexes were observed during crystallization of glutardiamidoxime with UO 2 (NO 3 ) 2 , where the metal nitrate induced in situ cyclization of the ligand to form a bridged dinuclear species (Figure 17). 132 While DFT and small molecule results are consistent with each other, it is worth noting they are performed under idealized conditions and may not be representative of a complex and dynamic system, as is the case for a polymer adsorbent deployed in seawater.…”
Section: Synthetic Polymersmentioning
confidence: 61%
“…The uranyl-binding ligand is formed by an in situ cyclization reaction of glutardiamidoxime prior to crystallization. Figure reprinted with permission from ref . Copyright 2016, Royal Society of Chemistry.…”
Section: Synthetic Polymersmentioning
confidence: 99%
“…Our data thus suggests that high Fe adsorption (Figure ) may cause much more pronounced amidoxime degradation. A recent report indicated that transition metals such as Cu­(II) and Ni­(II) can convert glutardiamidoxime, a single molecule surrogate of branch-chain amidoxime, to diiminopoperidin-1-ol under ambient conditions and may influence uranium adsorption by amidoxime ligand . The mechanism responsible for the Fe-induced amidoxime degradation and the subsequent poor adsorbent reusability are not clear and warrant further investigation.…”
Section: Resultsmentioning
confidence: 88%
“…A recent report indicated that transition metals such as Cu(II) and Ni(II) can convert glutardiamidoxime, a single molecule surrogate of branch-chain amidoxime, to diiminopoperidin-1ol under ambient conditions and may influence uranium adsorption by amidoxime ligand. 36 The mechanism responsible for the Fe-induced amidoxime degradation and the subsequent poor adsorbent reusability are not clear and warrant further investigation. On the other hand, the percent decreases of I 928 and I 1643 /I 1559 of AI8 adsorbent from humic acid-spiked seawater are only slightly higher than those from the unspiked seawater; the observed minor change in amidoxime abundance is reflected by the high reusability of AI8 under high HA conditions.…”
Section: Bicarbonate Elution For Adsorbent Regenerationmentioning
confidence: 99%
“…This treatment process is also known to generate cyclic imide dioxime sites (TEVWAU) which have been ascribed with exceptional affinity for uranium as well, [28][29][30] as demonstrated by rigorous titration experiments by Rao, et al [31][32][33] Finally, work by Warner and colleagues articulated the metal-catalyzed cyclization of two adjacent amidoximes on glutardiamidoxime to form 2,6-diiminopiperidin-1-ol, and the subsequent uranium binding and crystallization to form oxo-bridged dinuclear uranyl complexes (ONILUU). 34 Fig. 1 displays representative crystal structures from the aforementioned small molecule studies.…”
mentioning
confidence: 99%